Safety of celecoxib versus traditional nonsteroidal anti-inflammatory drugs in older patients with arthritis - Shin, Sooyoung (Journal of Pain Research, 2018)
Background: A 2011 systematic review found an increased cardiovascular (CV) risk at both ≤200 mg/day and >200 mg/day doses of celecoxib. This study aimed to evaluate adverse drug events with celecoxib relative to traditional nonsteroidal anti-inflammatory drugs (NSAIDs) in real-world practice settings, focusing on gastrointestinal (GI), CV, and renal toxicity, in older patients with osteoarthritis or rheumatoid arthritis. Methods: In this population-based retrospective cohort study using national health insurance claims data in Korea, patients aged 65 years and older with arthritis who were treated with celecoxib or traditional NSAIDs for ≥30 days in 2016, were included for study analyses. The primary outcome was hospital encounter for GI bleeding associated with celecoxib vs traditional NSAIDs use. The secondary outcomes included a composite of CV diseases, coronary revascularization, and incident renal events. Results: After 1:1 propensity score matching, 73,748 patients in each cohort were identified for study entry. Celecoxib treatment which lasted for ≥120 days was associated with a lower risk of GI bleeding than traditional NSAIDs (OR=0.84, P=0.03). Such a relationship was not observed in shorter treatment strata and overall in all strata combined. When patients with gastroprotective prophylaxis were excluded from subgroup analysis, no evidence of improved GI tolerability was observed with celecoxib. CV and renal risks appeared higher with celecoxib than with traditional NSAIDs (OR=1.08, P<0.001 and OR=1.22, P<0.001, respectively). About 4.7 % of celecoxib users received a higher than maximum dose (400 mg/day); a dose-dependent increase in CV and renal risks was assessed with celecoxib. Conclusion: Celecoxib was associated with decreased risk of GI bleeding compared with traditional NSAIDs when treatment lasted for ≥120 days, but such a relationship was not found among subgroup patients with no concomitant use of gastroprotective prophylaxis. Celecoxib users were more likely to experience CV and renal events than traditional NSAIDs users, and a dose-dependent risk relationship was observed with celecoxib.
Keywords: Adverse drug events; Celecoxib; Nonsteroidal anti-inflammatory drug; NSAID; Osteoarthritis; Rheumatoid arthritis